Integrating Ethics of Technology into a Serious Game: The Case of Tethics - Perperidis Giannis; Spilios Iason; Simos Manolis; Tympas Aristotle (Open Philosophy, 2025)
In the face of what is called “Existential risks/threats” or “polycrisis” – where digitalization, biomedicalization, and environmental degradation intertwine as existential threats – this article argues for a critical philosophy of technology as a necessary framework for ethical engagement. To address this polycrisis, we elaborate on an approach that integrates ethics and technology through serious gaming. Specifically, we introduce Tethics, a board game designed to engage players in ethical reflection on technological governance. By embedding critical philosophical insights into interactive gameplay, Tethics fosters a dynamic, experiential understanding of ethical dilemmas. Drawing on Andrew Feenberg’s critical theory of technology, we outline how game design can serve as a method for both refining philosophical inquiry and fostering public engagement. We argue that serious games may offer a unique means of interrogating and reconfiguring our relationship with technology, or can successfully act as educational tools for the ethics of technology today. Finally, we argue that Tethics performs a philosophically therapeutic function, debunking the metaphysical underpinnings of an instrumentalist and determinist viewpoint that dominates the current understanding of technology.